Does the volume of supplemental intraligamentary injections affect the anaesthetic success rate after a failed primary inferior alveolar nerve block? A randomized‐double blind clinical trial. (25th May 2017) - Aggarwal, V.; Singla, M.; Miglani, S.; Kohli, S.; Sharma, V.; Bhasin, S. S.
Abstract: Aim: To investigate the efficacy of 0.2 mL vs. 0.6 mL of 2% lidocaine when given as a supplementary intraligamentary injection after a failed inferior alveolar nerve block (IANB). Methodology: Ninety‐seven adult patients with symptomatic irreversible pulpits received an IANB and root canal treatment was initiated. Pain during treatment was recorded using a visual analogue scale (Heft‐Parker VAS). Patients with unsuccessful anaesthesia ( n  = 78) randomly received intraligamentary injection of either 0.2 mL or 0.6 mL of 2% lidocaine with 1 : 80 000 epinephrine. Root canal treatment was reinitiated. Success after primary injection or supplementary injection was defined as no or mild pain (HP VAS score ≤54 mm) during access preparation and root canal instrumentation. Heart rate was monitored using a finger pulse oximeter. The anaesthetic success rates were analysed with Pearson chi‐square test at 5% significance levels. The heart rate changes were analysed using t ‐tests. Results: The intraligamentary injections with 0.2 mL solution gave an anaesthetic success rate of 64%, whilst the 0.6 mL was successful in 84% of cases with failed primary IANB. (χ 2  = 4.3, P  = 0.03). There was no significant effect of the volume of intraligamentary injection on the change in heart rate. Conclusions: Increasing the volume of intraligamentary injection improved the success rates after a failed primary anaesthetic injection.